간호사의 아동 통증 중재에 대한 지식 및 태도 - 신희선; 김동희; Shin Hee-Sun; Kim Dong-Hee (Adong Kanho Hakhoe chi, 2003)
Purpose: The purpose of this study was to examine the nurses' knowledge and attitude to pain management in children and explore the status of pain management in clinical practice. Method: The subjects were 131 nurses enrolled in 3 university affiliated hospitals. Questionnaire method was utilized for data collection. Data was analyzed by SPSS statistical program. Result: The result was as follows: 1. The overall mean score of the pain knowledge was 16.88 (58.2％). The percentages of correct response in test subsections were pain assessment 45.5, choice of medication and drug action 48.7, and pain statement 79.6 respectively. 2. 70.3％ of the nurses agreed or strongly agreed that the procedural pain should always be eliminated. And, 44.3％ of the nurses agreed or strongly agreed that post-operative treatment of pain in children should always aim at eliminating the pain completely. 3. There was a significant relationship between pain attitude and knowledge related facts about pain(r=.217, p<.01). 4. When asked to identify the point of self-reported pain on a 0-10 scale at which the nurse would give medication, point 7 was mostly identified (29％). 5. Only 19.8％ of the nurses utilized pain rating scale to assess children's pain. 6. The nonpharmacologic interventions nurses used most were position change, emotional support, and massage. 7. 68.7％ of the nurses indicated that they learned about pain management from their current working environment. Also, Mostly helpful resource identified in increasing their pain management knowledge and skills was the continuing education program. Conclusion: The findings showed that there was a need to develop educational program for adequate pain management for children. Further research study is recommended to examine the effectiveness of the intervention methods for children's pain.